2009
DOI: 10.1128/jcm.02304-08
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Cefoxitin MICs with the Presence of mecA in Staphylococcus spp

Abstract: This report describes the results of an 11-laboratory study to determine if a cefoxitin broth microdilution MIC test could predict the presence of mecA in staphylococci. Using breakpoints of <4 g/ml for mecA-negative and >6 or 8 g/ml for mecA-positive isolates, sensitivity and specificity based on mecA or presumed mecA for Staphylococcus aureus at 18 h of incubation were 99.7 to 100% in three cation-adjusted Mueller-Hinton broths tested. For coagulase-negative strains at 24 h of incubation, breakpoints of <2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
12
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 6 publications
2
12
1
Order By: Relevance
“…However, detection of MR CoNS is problematic and less reliable than the detection of MR Staphylococcus aureus (1,2). Cefoxitin susceptibility testing has greatly improved the reliability of detecting MR S. aureus and, to a lesser extent, CoNS (3,4). Current CLSI guidelines recommend the use of cefoxitin disk testing for detecting MR CoNS, with some evidence that cefoxitin MIC determination can serve the same purpose (3,5).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, detection of MR CoNS is problematic and less reliable than the detection of MR Staphylococcus aureus (1,2). Cefoxitin susceptibility testing has greatly improved the reliability of detecting MR S. aureus and, to a lesser extent, CoNS (3,4). Current CLSI guidelines recommend the use of cefoxitin disk testing for detecting MR CoNS, with some evidence that cefoxitin MIC determination can serve the same purpose (3,5).…”
mentioning
confidence: 99%
“…Cefoxitin susceptibility testing has greatly improved the reliability of detecting MR S. aureus and, to a lesser extent, CoNS (3,4). Current CLSI guidelines recommend the use of cefoxitin disk testing for detecting MR CoNS, with some evidence that cefoxitin MIC determination can serve the same purpose (3,5). A number of studies have shown that cefoxitin disk testing of CoNS is generally sensitive but can be nonspecific (3,4,6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of the FOX test to detect this kind of low-level OR should be confirmed in a larger study. Concerning the CNS strains, the contribution of the FOX tests (DDM and panel PC30) was poor, as previously reported (21). However, the number of strains was insufficient to draw any conclusion, the limited power rendering irrelevant the meaning of the not-significant P value.…”
mentioning
confidence: 79%
“…Recently, a MIC value of 4 g/ml was established for FOX to detect the presence of the mecA gene (21). In the study of Swenson et al, only 0.3% (1/312) of mecA-positive S. aureus isolates showed a FOX MIC inferior to this breakpoint (21).…”
mentioning
confidence: 99%